Prediction for understanding the effectiveness of antiviral peptides. (December 2021) - Nath, Abhigyan
Abstract: The low efficacy of current antivirals in conjunction with the resistance of viruses against existing antiviral drugs has resulted in the demand for the development of novel antiviral agents. Antiviral peptides (AVPs) are those bioactive peptides having virucidal activity and they can be developed into promising antiviral drugs. They are shorter length peptides having the ability to cease the progression of viral infections. The use of antiviral peptides in therapeutics has recently attracted the attention of the research community. The development and identification of AVPs is imperative for the discovery of novel therapeutics for viral infections. In the present work, a meta classifier (stacking) based approach is implemented for the prediction of IC50 (half maximal inhibitory concentration) and pIC50 (negative log of half maximal inhibitory concentration) values. The best prediction model with evolutionary information and local alignment scores as features achieved a correlation coefficient values of 0.670 and 0.753 on the training and testing sets respectively for IC50 . Further, the prediction of pIC50 reached a correlation coefficient value of 0.797 and 0.789 for training and testing sets respectively. For the development of machine learning models involved in the prediction of IC50, the use of pIC50 over IC50 is recommended as the target variable. Further on a systematic comparison of AVPs with high IC50 values and Low IC50 values, it is revealed that higher mean charge and tiny amino acids are preferred and higher length and consecutive hydrophilic amino acids are avoided in the former. Graphical Abstract: ga1 Highlights: Enhanced prediction of IC50 . Prediction model for pIC50 . Systematic comparison between different IC50 groups. Preference/Avoidance of sequence features among different IC50 groups.